Gut Microbiota Composition and Structure of the Ob/Ob and Db/Db Mice. (11th March 2019) - Yang, Mingsheng; Liu, Yixin; Xie, Hengchang; Wen, Zhengzheng; Zhang, Yunxia; Wu, Changjing; Huang, Li; Wu, Jie; Xie, Chensheng; Wang, Tao; Peng, Weifeng; Liu, Shangqi; et al.
Abstract : Introduction. Gut microbiota is involved in the progression of metabolic diseases such as obesity and type 2 diabetes. The ob/ob and db/db mice are extensively used as models in studies on the pathogenesis of these diseases. The goal of this study is to characterize the composition and structure of gut microbiota in these model mice at different ages. Materials and methods. High-throughput sequencing was used to obtain the sequences of the highly variable 16S rRNA V3-V4 region from fecal samples. The taxa with high abundance in both model mice were identified by bioinformatics analysis. Moreover, the taxa with divergent abundance in one model mice at different ages or in both model mice at the same age were also recognized. Discussion and conclusion. The high abundance of Bacteroidetes and Firmicutes in microbiota composition and their imbalanced ratio in both model mice reflect the state of metabolic disorders of these mice. Differences in microbiota composition between the two model mice of the same age or in one model mice with different ages were assumed to be closely linked to the fluctuation of their blood glucose levels with age. The data on gut microbiota in ob/ob and db/db mice investigated herein has broad implications for the pathogenesis study and drug discovery on obesity and related complications.